Use of implementation science in tobacco control intervention studies in the USA between 2000 and 2020: a scoping review protocol. Issue 11 (11th November 2020) - Selove, Rebecca; Neil-Sztramko, Sarah; Leng, Jennifer; Walker, Philip D; Salloum, Ramzi George; Ginossar, Tamar; Heckman, Carolyn; Scheuermann, Taneisha S; Combs, Todd; Qualls-Hampton, Raquel; Armstrong, Rebecca; Ellis, Shellie
Abstract: Introduction: Despite continuing efforts to reduce tobacco use in the USA, decline in smoking rates have stalled and smoking remains a major contributor to preventable death. Implementation science could potentially improve uptake and impact of evidence-based tobacco control interventions; however, no previous studies have systematically examined how implementation science has been used in this field. Our scoping review will describe the use of implementation science in tobacco control in the USA, identify relevant gaps in research and suggest future directions for implementation science application to tobacco control. Methods and analysis: Our team, including a medical research librarian, will conduct a scoping review guided primarily by Arksey and O'Malley's methodology. We will search English language peer-reviewed literature published from 2000 to 31 December 2020 for terms synonymous with 'tobacco use', 'prevention', 'cessation' and 'implementation science'. The databases included in this search are MEDLINE (PubMed), Embase (Ovid), CINAHL (EBSCOhost), PsycINFO (ProQuest), ERIC (ProQuest) and the Cochrane Library (Wiley). We will include cohort and quasi-experimental studies, single-group experiments and randomised trials that report qualitative and/or quantitative data related to applying implementation science to the planning and/or delivery of interventions to prevent or decrease the use of tobacco products. Studies must target potential or active tobacco users, intervention providers such as educators or healthcare professionals, or US policy-makers. A minimum of two reviewers will independently examine each title and abstract for relevance, and each eligible full text for inclusion and analysis. Use of implementation science, demonstrated by explicit reference to implementation frameworks, strategies or outcomes, will be extracted from included studies and summarised. Ethics and dissemination: This study is exempt from ethics board approval. We will document the equity-orientation of included studies with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Equity Extension checklist. Results will be submitted for conferences and peer-reviewed journals. Trial registration number: Open Science Framework Registry (6YRK8).